Family business by the numbers : how financial statements impact your business - Schwarz, Norbert E. (New York : Palgrave MacMillan, 2011)
'Business is the language of numbers-but not everyone in businesses understands how to read the myriad of financial statements that are necessary. Author Norb Schwarz provides readers with accessible information to understanding financial statements such as annual reports; cash flow statements; income statements; balance sheets and so much more. Filled with accessible information including definition and explanations-this book is essential for all family businesses members who don't have a firm handle on these essential skills'--Provided by publisher.
Originally published: Marietta, GA. : Family Enterprise Publishers, 2004.
Includes index.
Keywords: Family-owned business enterprises -- Finance; Family-owned business enterprises -- Management; Financial statements